Interstellar Boundary Explorer (IBEX) may have recorded a cross-tail current disruption event of the substorm - Lu Li (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2023)
The spatial and temporal variations of satellite measurements correspond to different physical connotations. ENA imaging is an effective method to avoid the confusion of spatial and temporal variations of plasma space distribution in remote sensing region. However, for the neutral atom imager with scanning sampling, if the sampling time is too long (such as exceeding the evolution period of related physical events), it is still necessary to carefully analyze the time change factors of the space environment during the sampling period. Our re-certification of ENA scanning images of the IBEX-Hi's "terrestrial plasma sheet disconnection" revealed that a magnetospheric substorm occurred during sampling, most likely due to the pitch angle diffusion of energetic ions in the ring current to create the so-called "plasma sheet disconnection" illusion. The observation of ENA imaging reflects the motion pattern of its parent ions, which have a certain distance from space plasma visualization. The dynamic evolution of ring current energetic ion diffusion has inspired us to create a new macroscopic model of substorms that can be visually monitored in the ecliptic plane using ENA imaging.